ANALISIS PEGARUH BETA DAN RASIO KEUANGAN TERHADAP RETURN SAHAM INDEKS KOMPAS 100 - Lois Anjela Sembiring; Syarief Fauzie (Departemen Ekonomi Pembangunan USU, 2015)
The object of this study is to analyze the effect of beta and financial ratios on the stock return in Kompas 100 index. Financial ratios used are Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT) and Equity Per Share (EQPS). The data used were 46 companies selected using purposive sampling technique with the criteria (1) The companies whose shares are included in Kompas 100 index registered in Indonesia Stock Exchange during period 2009-2011. (2) The companies which were consistently active during period 2009-2011 in Kompas 100 index. (3) The companies fulfilling the indicator of dependent and independent variables during period 2009-2011. The data to analyze in this research were panel data using Multiple Linier Regression with Fixed Effect Model (FEM). Data processing was done using Eviews 7 program. The results of research showed that simultaneously through f-statistic test the variable of beta, current ratio, debt to equity ratio, total asset turnover and equity per share had significant influence to stock return in Kompas 100 index on significance rate 90%, whereas based on t-statistic test, it can be concluded that the variable of debt to equity ratio, total asset turnover and equity per share had significant influence to stock return in Kompas 100 index, and the variable of beta and current ratio had insignificant influence to stock returns in Kompas 100 index during period 2009-2011 on significance rate 95%. In addition, the coefficient of determination showed that the variable of beta, current ratio, debt to equity ratio, total asset turnover and equity per share are capable only to explain that the variable of stock return in Kompas 100 index for 44.25%.Keywords : Stock Return, Beta, Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Equity Per Share